Episode 2: climate conversations: Tufts' ban on direct coal investments and winter weather trends - Tufts Daily (Tufts Archival Research Center, 2021)
On this episode of "The Rewind," we explore Tufts' Feb. 10 commitment to ban direct investment in coal and tar sands with Tufts Daily reporter Alicia Zou and Tufts Climate Action representative Grace Abe. We continue our climate discussion as The Rewind's Ty Blitstein talks with Daily reporters Katie Furey and Keira Myles about the winter weather. Stay tuned weekly for more stories from the Tufts Daily.